Diagrams for logics - Sato, Yuri; Mineshima, Koji (Cognitive Studies: Bulletin of the Japanese Cognitive Science Society, 2020)
The use of diagrams, instead of linguistic and symbolic representations, in logical reasoning has been the subject of continuous research interest over the last few centuries. Especially in 1990s, such logic diagrams have attracted substantial research attention in the fields of logic, artificial intelligence and cognitive science. More recently, according to some applications to computer sciences, various diagrammatic systems have been developed to handle extended types of logical information and reasoning. The research direction of logic diagram design raises the question of to what extent diagrammatic systems can be expressive enough to handle the generality of logics as well as be natural and effective so that they are easy to understand. This paper surveys historical and recent developments of logic diagrams, focusing on the two types of visualization: Euler/Venn diagrams and graph representations. While a majority of previous researches on cognitive science of reasoning focus on linguistic forms, this survey provides a systematic overview of diagrammatic reasoning, contributing to understanding the theoretical basis of reasoning in visual forms.